QUALITY OF LIFE AT WORK: PERCEPTION OF NURSES AND NURSING TECHNICIANS FROM A HOSPITAL IN SERRA GAÚCHA, RS - Migowski, Eliana Rustick; Piccoli, João Carlos Jaccottet; Quevedo, Daniela Müller de (Saúde (Santa Maria), 2016)
The present descriptive, cross-sectional study aims to analyze the quality of work life (QLW) with 95 nurses and nurse technicians selected by convenience from a hospital in Serra Gaúcha, RS. The Nursing Questionnaire of quality of life at work (QWLQ-78) was used and divided into four domains (Physical/Health; Psychological; Professional; and Personal). The data were submitted to descriptive statistics (means and standard deviations) and absolute and relative frequency calculation. The results from all domains showed a satisfactory perception of quality of life at work (QLW). A strong correlation was observed between all domains and QLW, notably in the personal domain (r=0,866), followed by Psychological and Professional Domains (both ρ=0.819). The lowest correlation occurred between the Physical/Health domain and QWL (r=0.762) and between this domain and the others. The study showed a satisfactory perception of QWL in the studied sample. Descriptors: Quality of Life; Hospital; Nursing.